Rationalist Interpretation of Rubūbiyyah in Al-Zamakhshari’s Al-Kashshāf: A Theological Analysis of Monotheistic Discourse - Masruchin (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2025)
Monotheism is a central tenet of Islamic theology, with various scholars offering distinct interpretations of its dimensions. This study explores the concept of Rubūbiyyah (Divine Lordship) as presented in Al-Kashshāf, the seminal Qur'anic exegesis by Al-Zamakhshari. It aims to analyze how Al-Zamakhshari’s rationalist approach shapes his theological interpretation of Rubūbiyyah and to what extent it aligns with or diverges from classical Islamic theological thought. Employing a qualitative library research method, this study utilizes descriptive and content analysis to examine relevant exegetical passages. The findings indicate that while Al-Kashshāf offers a rationalist reading rooted in Mu'tazilite principles and external philosophical influences, it does not fully capture the broader metaphysical and spiritual dimensions of Islamic monotheism. Nevertheless, Al-Zamakhshari consistently grounds his interpretations in Qur'anic text, reflecting a commitment to scriptural authority. This study contributes to the discourse on Qur'anic interpretation by highlighting the interplay between rationalism and theology, and by offering critical insights into the theological methodology embedded in Al-Zamakhshari’s exegesis.